Crop nutrition and fertilizer management of embryo-cultured seedlings of Makapuno and Laguna Tall coconuts with special reference to their response to different levels of NaCl and chicken manure - M. B. Areza-Ubaldo; S. S. Magat; E. P. Rillo; M. I. Secretaria (International Coconut Community Journal, 2006)
A two-year nursery study of embryo-cultured Laguna Tall (ECLAGT) and embryo-cultured Makapuno Tall (ECMAKT) coconut seedlings was conducted at the Philippine Coconut Authority - Albay Research Center, Guinobatan, Albay aimed to know the effects of applying different levels of sodium chloride (NaCl) (common table salt) and chicken manure (CM) on the vegetative growth and leaf nutrient status of the seedlings. The soil used in the study is a volcanic ash- rich Guinobatan silt loam, classified as Entic Dystrandept soil subgroup (U.S. Soil Taxonomy/Classification). EC seedlings with the application of NaCl at a total dose of 18-54 g/seedling and chicken manure at 250-750 g/seedling, applied within the 12-month nursery (at intervals of 2,4,6,8,10 months) significantly produced taller seedlings with bigger girth and more total living fronds than the unfertilized ECLAGT and ECMAKT seedlings. The levels of nutrient application (fertilization) on EC seedlings is clearly much lower than that of the average rates used in growing ordinary seedlings from seednuts, i.e. seedling with embryo attached to the whole nut in the nursery. The better growth of ECLAGT and ECMAKT seedlings in terms of their girth, plant height and total living fronds produced was significantly associated with higher or very satisfactory levels of leaf N, P, K, Cl, Ca, Na, Mg, S, B, and Fe (leaf #4 of 12-month old EC seedlings). The overall results clearly indicate the practical need to apply a combination of sodium chloride and dried chicken manure, even at moderate rates (total) of 18 g/seedling and 250 g/seedling respectively, divided equally during the 12-month nursery stage for normal growth and proper nutrition of EC seedlings. This recommended fertilization management practice should ensure healthy and good quality ECMAKT seedlings as planting materials.